Metabolism, pharmacokinetics, and anticonvulsant activity of a deuterated analog of the α2/3‐selective GABAkine KRM‐II‐81. (10th March 2022) - Golani, Lalit K.; Divović, Branka; Sharmin, Dishary; Pandey, Kamal P.; Mian, Md Yeunus; Cerne, Rok; Zahn, Nicolas M.; Meyer, Michelle J.; Tiruveedhula, Veera V. N. P. B.; Smith, Jodi L.; Ping, Xingjie; Jin, Xiaoming; et al.
Abstract: The imidazodiazepine, (5‐(8‐ethynyl‐6‐(pyridin‐2‐yl)‐4H‐benzo [ f ]imidazole[1, 5‐α][1, 4]diazepin‐3‐yl) oxazole or KRM‐II‐81) is a new α2/3‐selective GABAkine (gamma aminobutyric acid A receptor potentiator) with anticonvulsant, anxiolytic, and antinociceptive activity in preclinical models. Reducing metabolism was utilized as a means of potentially extending the half‐life of KRM‐II‐81. In vitro and in vivo studies were conducted to evaluate metabolic liabilities. Incubation of KRM‐II‐81 in hepatocytes revealed sites of potential metabolism on the oxazole and the diazepine rings. These sites were targeted in the design of a deuterated analog (D5‐KRM‐II‐81) that could be evaluated as a potentially longer‐acting analog. In contrast to computer predictions, peak plasma concentrations of D5‐KRM‐II‐81 in rats were not significantly greater than those produced by KRM‐II‐81 after oral administration. Furthermore, brain disposition of KRM‐II‐81 was higher than that of D5‐KRM‐II‐81. The half‐life of the two compounds in either plasma or brain did not statistically differ from one another but the tmax for D5‐KRM‐II‐81 occurred slightly earlier than for KRM‐II‐81. Non‐metabolic considerations might be relevant to the lack of increases in exposure by D5‐KRM‐II‐81. Alternative sites of metabolism on KRM‐II‐81, not targeted by the current deuteration process, are also possible. Despite its lack of augmented exposure, D5‐KRM‐II‐81, like KRM‐II‐81, significantly prevented seizures induced by pentylenetetrazol when given orally. The present findings introduce a new orally active anticonvulsant GABAkine, D5‐KRM‐II‐81. Abstract : KRM‐II‐81 is under development for epilepsy and other neurological disorders. A deuterated analog was constructed from the aldehyde (compound 1) with the goal of blocking computer‐predicted sites of metabolism. Although deuteration of these sites did not significantly modify metabolism, suggesting alternative metabolic vulnerabilities, D5‐KRM‐II‐81, like KRM‐II‐81, was an orally active anticonvulsant in mice.